Complement activation in association with clinical outcomes in ST-elevation myocardial infarction - Karsten E. Kluge; Miriam S. Langseth; Geir Ø. Andersen; Sigrun Halvorsen; Trine B. Opstad; Harald Arnesen; Theis Tønnessen; Ingebjørg Seljeflot; Ragnhild Helseth (American Heart Journal Plus, 2022)
Introduction: The complement system and neutrophil extracellular traps (NETs) might contribute to ischemia-reperfusion injury in ST-elevation myocardial infarction (STEMI). We aimed to estimate associations between complement activation and NETs in STEMI, and their prognostic value on clinical endpoints. Methods: In this cohort study, 864 patients admitted for PCI during STEMI were included. Complement activation was analyzed by the terminal complement complex (TCC), while NETs were analyzed by myeloperoxidase-DNA, citrullinated histone 3 (CitH3) and dsDNA. The composite endpoint was reinfarction, unscheduled revascularization, stroke, hospitalization due to heart failure, or death, and the secondary endpoint was total mortality. The association between TCC and clinical endpoints was assessed by Cox regression and ROC curve analysis. Results: TCC was weakly correlated to dsDNA (r = 0.127, p < 0.001) and CitH3 (r = 0.102, p = 0.003). After a median follow-up time of 4.6 years, 184 (21.3 %) patients had reached a clinical endpoint. TCC was not associated with the composite endpoint, but with total mortality (HR: 1.673, 95 % CI: [1.014, 2.761], p = 0.044). The significant association was lost when adjusting for CRP, NT-proBNP, LVEF and time from symptoms to PCI. In ROC curve analysis of total mortality, the AUC for TCC alone was 0.549 (95 % CI: [0.472, 0.625]), AUC for dsDNA alone was 0.653 (95 % CI: [0.579, 0.720]), while AUC for TCC and dsDNA combined was 0.660 (95 % CI: [0.590, 0.730]). Conclusions: In this STEMI cohort, TCC was not associated with the composite endpoint, but somewhat with total mortality. Combining TCC and dsDNA did not increase the prognostic value compared to dsDNA alone.